Pengaruh Tingkat Inflasi, Nilai Tukar, dan Reksadana Syariah Terhadap Harga Saham ( Studi Kasus Pada Sub-Sektor Industri yang Terdaftar di BEI Periode 2018-2021 ) - Moh Nauval Zabidi; Citra Mulya Sari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was to determine the extent of the influence of inflation, exchange rates, and Islamic mutual funds on stock prices in 2018-2021. The type of research in this study is quantitative research and data analysis techniques in this study using panel data analysis through Eviews. The results of this study indicate that Inflation, Exchange Rates, and Sharia Mutual Funds simultaneously have a significant effect on the 2018-2021 Stock Price. Based on the t-test in this study, it shows that inflation (X1) has no significant effect on the 2018-2021 stock price. And for the Exchange Rate variable (X2), it has a significant effect on the 2018-2021 Stock Price. Sharia Mutual Funds variable (X3) has no significant effect on the 2018-2021 stock price. Keywords: Inflation, Exchange Rate, Sharia Mutual Funds, Stock Prices